ANALISIS PERENCANAAN PENGELOLAAN KEUANGAN DESA SESUAI DENGAN PERATURAN MENTERI DALAM NEGERI NOMOR 113 TAHUN 2014 DI DESA KAUNERAN I KECAMATAN SONDER KABUPATEN MINAHASA - Walukow, Mewvi I.; Kalangi, Lintje; Pinatik, Sherly (Universitas Sam Ratulangi, 2017)
Village financial management planning is the first step in the village financial management process. This planning stage is very important because in relation to village financial management, this stage of planning is the process by which the draft APBDesa will be developed. The purpose of this research is to know the financial planning in Kauneran I village, Sonder sub-district of Minahasa regency. This research uses qualitative analysis method. The results showed that at the planning stage of village financial management in the village of Kauneran I still not in accordance with Permendagri 113/2014. This is seen in the government regulations on APBDesa that should be evaluated by the local Bupati / Walikota is not implemented at all. In addition, the lack of participation from the community also becomes another fator of constraints in the planning stages of village finance management. This indicates that the financial management of villages in Kauneran I village has not implemented a participatory principle in accordance with Permendagri 113/201.Keyword: Perencanaan Village’s Financial Management, Permendagri No. 113/2014